Proposed Office Facilities Layout in Low Voltage Electric Panel Manufacturer - Julliete Angel Luin; Josephine Angel Luin (JIEMS (Journal of Industrial Engineering and Management Systems), 2021)
The electrical equipment industry in Indonesia is one of the factors that triggers economic growth. Labor productivity determines the success of project implementation. The non-optimal facility layout is one of the factors that triggers low labor productivity. The non-optimal facility layout affects the flow of information in the company. This study examines the problem of non-optimal office facility layout with TSP, ARC and ARD methods at PT. Duta Wijaya Elektrindo Engineering (PT. DWP). The method stated above can minimize the total distance traveled between office facilities so that work efficiency and workforce productivity may increase. The results of data processing indicate that the recommended office facility layout recommendations that are in accordance with the level of closeness between departments based on PST, ARC and ARD is the first recommendation. With reduced total distance traveled in the first layout of the proposed office facilities, the level of employee productivity and work efficiency will increase. The smallest total distance traveled on the proposed layout of the office facilities is 244.22 meters with a reduction of 36% from the initial conditions.